2012
DOI: 10.1038/ncb2590
|View full text |Cite|
|
Sign up to set email alerts
|

Liver cancer initiation is controlled by AP-1 through SIRT6-dependent inhibition of survivin

Abstract: Understanding stage-dependent oncogenic mechanisms is critical to develop not only targeted therapies, but also diagnostic markers and preventive strategies. The mechanisms acting during cancer initiation remain elusive, largely owing to a lack of suitable animal models and limited availability of human precancerous lesions. Here we show using genetic mouse models specific for liver cancer initiation, that survival of initiated cancer cells is controlled by c-Jun, independently of p53, through suppressing c-Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
189
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(200 citation statements)
references
References 39 publications
10
189
1
Order By: Relevance
“…The increase in SIRT6 impairs cancer development by targeting the anti-apoptotic activity of survivin. Min et al 10 identified in human dysplastic liver nodules a specific expression pattern characterized by increased c-Jun-survivin and reduced cFos-SIRT6 level. In hepatocellular carcinoma (HCC), Bhardwaj et al 11 found that SIRT6 acts as a tumor suppressor because it deacetylates nuclear pyruvate kinase M2 (PKM2) inhibiting cell proliferation and tumorigenesis via PKM2.…”
Section: Sirt6 As a Tumor Suppressormentioning
confidence: 99%
“…The increase in SIRT6 impairs cancer development by targeting the anti-apoptotic activity of survivin. Min et al 10 identified in human dysplastic liver nodules a specific expression pattern characterized by increased c-Jun-survivin and reduced cFos-SIRT6 level. In hepatocellular carcinoma (HCC), Bhardwaj et al 11 found that SIRT6 acts as a tumor suppressor because it deacetylates nuclear pyruvate kinase M2 (PKM2) inhibiting cell proliferation and tumorigenesis via PKM2.…”
Section: Sirt6 As a Tumor Suppressormentioning
confidence: 99%
“…c-Fos is able to induce transcription of the Sirt6 gene; the sirtuin in turn represses survivin via NF-κB. The significance of apoptotic resistance regulation by AP-1-SIRT6 signalling in the survival of pre-neoplastic lesions is further strengthened by the observation that both display specific expression patterns in pathological tissue samples [134].…”
Section: Transcriptional and Post-transcriptional Regulators As Sirtumentioning
confidence: 99%
“…Previous studies have indicated that SIRT6 serves important roles in the development of cancer: SIRT6 expression is downregulated in a variety of types of cancer, including hepatic and breast cancer, and head and neck squamous cell carcinoma (9)(10)(11). Downregulation of SIRT6 is positively correlated with poor prognosis and low tumor-free survival rates in CRC and pancreatic ductal adenocarcinoma (12,13).…”
Section: Introductionmentioning
confidence: 99%